Ketangguhan Ruang Pusaka Saujana Danau Toba - Utami, Wahyu (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2019)
Cultural landscape heritage of Toba Lake Area is a series is a series of landscapes with community activities. It is about an area with its activities in a specific landscape that included by Toba Lake and its caldera with a landscape as a part of geology process into ancient eruption. Stage of cultural landscape process should be a significant focus for a balancing and equilibrium in environmental change. In this paper that supported by dialog theory between theories of tourism in cultural landscape area and resilience which take Toba Lake area as a case. Grounded research was used by cases exploration. Principally, spatial planning will be changing because of human activities and tourism activities. Changing in its livelihood was occurred because there were many demand for them. All the changes should be into a consideration for nature and livelihood with specific culture and belief. Tourism is set up with referring to equilibrium Toba Lake’s nature and its communities of Batak ethic group. Resilience has a goal to anticipate many changing so as the spatial planning and the communities can adapt with its capacities.